Association of Omega-3 Fatty Acid Levels with Cardiovascular Disease Risk Factors and Metabolic Syndrome among Adults - Fatima Inayat, Atiq Ahmad, Sadaf Hammad, Muhammad Ikram, Muhammad Naveed, Muhammad Anas Ahmed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Cardiovascular disease (CVD) remains a leading cause of morbidity and mortality worldwide. Omega-3 fatty acids (ω-3 FAs) have been suggested to have a beneficial effect on CVD risk factors and metabolic syndrome (MetS), but their role in adults remains unclear. Objective: To investigate the association of omega-3 fatty acid levels with cardiovascular disease risk factors and the prevalence of metabolic syndrome among a cohort of 243 adults. Methodology: This cross-sectional study was conducted at Shaikh Zayed Hospital, Lahore during January 2023 till August 2023. A total of 243 patients were added in the study. Data were collected using a combination of clinical assessments, laboratory tests, and self-reported questionnaires. Data collection for this study involved clinical assessments, laboratory tests, and self-reported questionnaires. Results: The mean age of 45 years ranging from 18 to 65 years. There were 55% females and 45% males. The mean body mass index was 27.5±4.2 kg/m², indicating that the majority were overweight or obese, with a range of 18.5 to 38.0 kg/m². Waist circumference measurements revealed an average of 94 cm for men and 88 cm for women, reflecting central obesity. The relationship between Omega-3 Index (O3I) levels and insulin resistance, as measured by HOMA-IR, revealed that participants with an O3I of less than 4% had a higher mean HOMA-IR of 2.2±1.1, with 35% of them exhibiting insulin resistance (HOMA-IR ≥2.5). In contrast, participants with O3I levels between 4-6% showed a mean HOMA-IR of 1.9±0.9, with 25% demonstrating insulin resistance. Those with an O3I of 6% or higher had the lowest mean HOMA-IR of 1.5±0.7, and only 15% had insulin resistance. Conclusion: Higher omega-3 fatty acid levels are inversely associated with cardiovascular disease risk factors and the prevalence of metabolic syndrome among adults. Omega-3 supplementation or dietary intake could be beneficial in mitigating cardiovascular and metabolic risks in the adult population. Keywords: Patients, Omega-3 Fatty acids, CVD, Metabolic, Syndrome